Tales of the Way of Death: ethnography and the translation of Amerindian poetry - Cesarino, Pedro de Niemeyer (Estudos Avançados, 2012)
The article addresses aspects of the ethnography and the translation of the poetry of Amerindian peoples from the South American lowlands, particularly the Marubo (Javari valley, Amazon). I begin with a brief review of theoretical perspectives that are central to understanding the subject and go on to argue that the work of translational re-creation of songs and narratives derived from oral performances should be carried out in tandem with the work of conceptual translation. Finally, I provide a bilingual rendering of a long narrative testimony on posthumous fate and the formation of the Way of the Dead ("The Reports of the Death-Path"), as given by Marubo shaman Armando Cherõpapa.